2020
DOI: 10.1007/s10055-020-00472-4
|View full text |Cite
|
Sign up to set email alerts
|

Social viewing in cinematic virtual reality: a design space for social movie applications

Abstract: Since watching movies is a social experience for most people, it is important to know how an application should be designed for enabling shared cinematic virtual reality (CVR) experiences via head-mounted displays (HMDs). Viewers can feel isolated when watching omnidirectional movies with HMDs. Even if they are watching the movie simultaneously, they do not automatically see the same field of view, since they can freely choose their viewing direction. Our goal is to explore interaction techniques to efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Exploring the adoption and benefits of all proposed solutions, including 3D radars as guiding methods, in 3D VR scenarios with 6DoF -or with much less limited 6DoF -, likes the ones presented and envisioned in [34].  Exploring accessibility solutions for social viewing scenarios, like the ones described in [29] and [35].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the adoption and benefits of all proposed solutions, including 3D radars as guiding methods, in 3D VR scenarios with 6DoF -or with much less limited 6DoF -, likes the ones presented and envisioned in [34].  Exploring accessibility solutions for social viewing scenarios, like the ones described in [29] and [35].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a more recent study [18] investigated the challenges and requirements for enabling shared 360º video consumption scenarios using head-mounted displays (HMDs) and by incorporating a set of guiding and interaction strategies.…”
Section: A Research On 2d Multi-party Conferencingmentioning
confidence: 99%
“…The work in [21] showed that the adoption of HMDs in conjunction with RGB-D cameras for the end-users' capturing and representation can lead to an increased engagement, feeling of immersion and enjoyable embodied telepresence compared to traditional 2D social viewing tools. The work in [25] analyzed the requirement and challenges to efficiently support shared media consumption of 360º videos using HMDs, and proposed guiding and interaction strategies to contribute to this. The work in [10] presented a video-based Social VR platform mainly focused on shared media consumption of stored content.…”
Section: )mentioning
confidence: 99%